Setaria viridis (L.) P. Beauv. (acesso A10.1) como potencial planta modelo para validação de promotores/genes responsivos ao estresse salino - Ferreira, Thalita Massaro Malheiros (2020)
This study aimed to test two hypotheses, which were: a) Setaria viridis (L.) P. Beauv. (accession A10.1) is not tolerant to salt stress, and therefore can be used as a model plant for validation of candidate genes to confer tolerance to salinity, and b) the expression profile of salinity stress-responsive genes from oil palm (Elaeis guineensis Jacq.), observed by in silico differential expression analysis, is the same as that observed in vivo. To test the first hypothesis, we performed the characterization of the morphophysiological response of S. viridis (A10.1) to different concentrations of NaCl in seed germination and initial development, as well as in the vegetative phase. The results achieved allow confirming the first hypothesis; however, besides seen that the seed germination was little affected by the salinity in the substrate, while the initial seedling development was highly impaired; it was also observed that in the vegetative phase the intolerance to salt was more evident when the electrical conductivity is greater than approximately 15 dSm-1 (NaCl > 0.4 g / 100 g substrate). To test the second hypothesis, we prospected and annotated genes responsive to salinity stress in the oil palm genome and then characterized its expression profile through qPCR analysis. RNA-seq data, which are part of Embrapa Agroenergy's “Salt of the Earth” Database, and which were obtained from leaf samples of plants with zero, five and twelve days of salt stress, were submitted to analysis using the OmicsBox platform transcript module. For the selection of saline stress-responsive genes, the following criteria were applied: FDR ≤ 0.01 and logFC ≥ 5. A total of 33 genes were selected when comparing plants at zero and five days of stress and 10 genes when comparing plants at zero and 12 days of stress. Six genes were common to both groups and were therefore selected for structural and functional annotation. From these, three genes were selected for characterization of the expression profile in vivo; none of them had coincidence in silico and in vivo expression profiles.